Pemberdayaan Komunitas Perempuan Sekar Ayu Membangun Literasi Kultural Upaya Meningkatkan Ekonomi Masyarakat - Sahiruddin, Sahir; Lilik Wayhuni; Nur Hikmah Arifin (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Sekar Ayu is a women's community that works to preserve Mojopahit culture by promoting cultural locality in Pesanggrahan Village. Activities organized by the leader of Sekar Ayu involve all members and the surrounding community. The empowerment initiatives include enhancing the local economy through women's creativity in producing unique, halal-certified food products. The research methodology employed a qualitative approach to interpret environmental phenomena from the perspective of local community interpretations in Songgoati, Mojokerto Regency. The empowerment programs implemented by Sekar Ayu include: (1) Empowering the Sekar Ayu women's community to build cultural literacy, (2) Empowering the women's community through Sekar Ayu's program activities, and (3) Empowering the women's community through the establishment of SMEs. The activities implemented as part of women's empowerment efforts aim to alleviate women's poverty and not only contribute to gender equality but also to inclusive and sustainable economic development.